Binocular misalignments elicited by altered gravity provide evidence for nonlinear central compensation - Beaton, Kara H.; Huffman, W. Cary; Schubert, Michael C. (Frontiers in Systems Neuroscience, 2015)
Increased ocular positioning misalignments upon exposure to altered gravity levels (g-levels) have been strongly correlated with space motion sickness (SMS) severity, possibly due to underlying otolith asymmetries uncompensated in novel gravitational environments. We investigated vertical and torsional ocular positioning misalignments elicited by the 0 and 1.8 g g-levels of parabolic flight and used these data to develop a computational model to describe how such misalignments might arise. Ocular misalignments were inferred through two perceptual nulling tasks: Vertical Alignment Nulling (VAN) and Torsional Alignment Nulling (TAN). All test subjects exhibited significant differences in ocular misalignments in the novel g-levels, which we postulate to be the result of healthy individuals with 1 g-tuned central compensatory mechanisms unadapted to the parabolic flight environment. Furthermore, the magnitude and direction of ocular misalignments in hypo-g and hyper-g, in comparison to 1 g, were nonlinear and nonmonotonic. Previous linear models of central compensation do not predict this. Here we show that a single model of the form a + bgε, where a, b, and ε are the model parameters and g is the current g-level, accounts for both the vertical and torsional ocular misalignment data observed inflight. Furthering our understanding of oculomotor control is critical for the development of interventions that promote adaptation in spaceflight (e.g., countermeasures for novel g-level exposure) and terrestrial (e.g., rehabilitation protocols for vestibular pathology) environments.